The shifting patterns based on six thinking hats and its relationship with design creativity. (December 2021) - Hu, Ying; Ren, Zhenzhen; Du, Xing; Lan, Lan; Yu, Wenyan; Yang, Shirao
Highlights: Participants would select and shift the hats according to different situations. The shifting patterns in different thinking-hat sets are different, which is related to the characteristics of these sets. Groups on different design creativity levels are different in the shifting relationships in shifting patterns. Abstract: Creativity and design are closely related. Some studies only focus on one component of creative thinking, but creativity is related to the interaction between various thinking processes, stimulate shifting between processes is an important way to study cultivate and enhance creativity. Therefore, the paper proposed a new way of using the thinking hats, and based on the team cooperation mode of individual group iteration, we collected and analyzed the shifting patterns of members in the group when thinking under the hats and the relationship between shifting relationships in shifting patterns and design creativity. The results showed that when facing the thinking-hat sets, participants would select and shift the hats according to different situations. And the shifting patterns in different thinking-hat sets are different, which is related to the characteristics of these sets. There are significant differences in shifting relationships between groups on different design creativity levels in some design creativity dimensions. In addition, we also found an interesting way to use the thinking-hat sets. The research results of the patterns of shifting between different types of thinking under the thinking-hat sets and the relationship between the shifting relationships in shifting patterns and design creativity can be used to formulate effective intervention measures and strategies to stimulate the process of shifting of group members, and applied to the classroom of future service design education to provide a new path for the cultivation and promotion of students' creativity.